Continuously Variable Transmission Roller Mass Analysis with Drive Pulley Angle Variations of 13.5° and 12° on a 150 cc V - Matic Automatic Transmission Motorcycle - Luchyto Chandra Permadi; Mojibur Rohman; Ratna Fajarwati Meditama; Bella Cornelia Tjiptady; Faisol Khoufi Asshidiqi; Mudrikah Mudrikah; Bagus Sriwijaya (Universitas Islam Raden Rahmat, Malang, 2026)
The Continuously Variable Transmission (CVT) system plays a crucial role in transmitting power from the engine to the drive wheels while automatically adjusting the transmission ratio according to vehicle speed and load conditions. Automatic transmissions have gained widespread attention in the automotive industry due to their high efficiency, smooth gear shifting, cost-effectiveness, and enhanced driving comfort. This study aims to investigate the effect of drive pulley angle variation and roller weight on the performance characteristics of a CVT system, particularly in terms of power output, torque, vehicle speed, and acceleration. An experimental method was employed by modifying the drive pulley angle and roller weight configurations, followed by performance testing using a dynamometer (dynotest). Several combinations of pulley angles and roller weights were evaluated to determine the optimal configuration for vehicle performance. The results indicate that a drive pulley angle of 13.5° combined with a 10-gram roller produced the most stable torque and power characteristics across low to high engine speeds. This configuration also provided superior acceleration performance and smoother power delivery under urban driving conditions. The findings offer practical insights for optimizing CVT design and tuning to improve vehicle efficiency, responsiveness, and overall driving performance.